Recognizing Level of Attachment in Malacca Riverfront Promenade - Nurakmal Abdullah, @ Goh Tuo Ho; Bambang, Karsono; Dona Rose, Amer Koesmeri; Zayn Al-Abideen, Gregory; Yon Syafni, Samat (UNIMAS Publisher, Universiti Malaysia Sarawak, 2019)
The present city development tends to be disintegrating and decreasing the quality of its attachment and meaning. It is important to recognize the level of place attachment in existing locality, to understanding the significance of place attachment in influencing the identities. This paper intends to determine the importance of level of functional and emotional attachment in Malacca Riverfront Promenade (MRP) from users who involved in it. Score average 2.70 as result of functional attachment and score average 2.48 of emotional attachment measurement, indicate that respondents have strong level of attachment to the functional and emotional of open space and streets in MRP. Most of the respondents consider that they feel more attached to MRP caused by the significance of MRP for their life. Attachment emerged from the role of MRP as an environment to determine the reason of respondent to attached and gain the experience in MRP.